GSK-J1-loaded, hyaluronic acid-decorated metal-organic frameworks for the treatment of ovarian cancer - Yang, Bing; Liu, Wenxu; Li, Meiying; Mo, Jingxin (Frontiers in Pharmacology, 2022)
Despite intensive research, ovarian cancer has the highest mortality rates among gynecological malignancies, partly because of its rapid acquisition of chemoresistance to platinum therapy. Hence, strategies are needed to effectively treat carboplatin-resistant ovarian cancer. In this study, we designed and prepared hyaluronic acid-decorated metal-organic frameworks for the targeted delivery of GSK-J1, a JMJD3 demethylase inhibitor (HA@MOF@GSK-J1) for the synergistic treatment of carboplatin-resistant ovarian cancer. HA@MOF@GSK-J1 showed outstanding effectiveness in the inhibition of ovarian cancer in vitro. Furthermore, HA@MOF@GSK-J1 demonstrated higher induction of apoptosis, reduced cell motility, and diminished cell spheroids by attenuating HER2 activity through the effectual activation of H3K27 methylation in its promoter area. Finally, our in vivo results confirmed that HA@MOF@GSK-J1 had better treatment efficacy for carboplatin-resistant ovarian tumor xenografts. Our results highlight the potential of HA@MOF@GSK-J1 as an effective strategy to improve the treatment of carboplatin-resistant ovarian cancer.